PENGARUH DIMENSI PERSEPSI KUALITAS PELAYANAN TERHADAP KEPUASAN PELAYANAN PESERTA PADA PROGRAM PENDIDIKAN KEWIRAUSAHAAN MASYARAKAT PADA LEMBAGA KURSUS DAN PELATIHAN DI KABUPATEN WONOGIRI - Slamet Djauhari, Sarsiti & (Universitas Slamet Riyadi, 2016)
This study aims to determine the service quality dimensions thatinfluence participant satisfaction waiter community entrepreneurshipeducation program at the Institute of Training Courses and Wonogiri. Thisstudy enhance the perception of service quality dimension refers to servqualby adding the dimension of perception of service quality and timeliness ofservice. Timeliness of service is considered to have a significant positiveeffect on satisfaction entrepreneurship education program participantcommunity. Courses and training institutions must pay attention to timelinessin providing services during the implementation of the program, with thehope of community entrepreneurship education program participants getsatisfaction as perceived by participants of community entrepreneurshipeducation program. Data analysis was conducted using classic assumptiontest, multiple linear regression, coefficient of determination, F test and t test.From the analysis of data and has escaped from the classical assumption, itcan be discussed for each of these hypotheses has been formulated.Judging from the t test factors of physical evidence and the timeliness ofpartial effect significant effect on service satisfaction entrepreneurshipeducation program participants society (PKM) on Courses and TrainingInstitute in Wonogiri Regency. While variable reliability, responsiveness,assurance and attention partially no significant effect on service satisfactionentrepreneurship education program participants society on Courses andTraining Institute in Wonogiri Regency. Viewed from the F test variablephysical evidence, reliability, responsiveness, assurance, and attentionsimultaneously significant effect on service satisfaction entrepreneurshipeducation program participants society on Courses and Training Institute inWonogiri Regency. Based on the determination coefficient indicates that thevariable physical evidence, reliability, responsiveness, assurance, attentionand timeliness affect the service satisfaction entrepreneurship educationprogram participants society on Courses and Training Institute in Wonogiriby 80,3% while the remaining 19,7% influenced by other variables that arenot used in the study.Keywords: service quality, satisfaction, dimensions program participant,PKM